Удосконалення моделей динаміки вібраційних двигунів з маятниковими вібраторами - Білоус, Андрій Борисович (Національний університет "Львівська політехніка", 2008)
У дисертації наведене теоретичне узагальнення і нове вирішення наукової задачі, що виявляється в удосконаленні моделей динаміки вібраційних двигунів з маятниковими вібраторами і МВХ при кінетичному, силовому - електромагнітному і змішаному збуреннях методами аналітичної механіки, математичного моделювання, аналітичного і чисельного розв’язкурівнянь і систем нелінійних диференціальних рівнянь другого порядку з імпульсними коефіцієнтами з постановкою чисельного і натурного експериментів, результати яких закладені в підвалини удосконалення методики проектного розрахунку цих двигунів. За результатами досліджень в практику використання впроваджена методика проектного розрахунку вібраційних двигунівз маятниковими вібраторами і МВХ при кінетичному, силовому – електромагнітному і змішаному збуреннях. Запропонована до використання методика дослідження механічних систем змінної структури. The theoretical generalization and new decision of scientific taskis resulted in dissertation. These thingsare basedin the improvement of oscillation engines with pendulum vibrators and mechanism of free motion (MFM) dynamics models withkinetic, power -electromagnetic and mixed indignations. Forimprovement of these models were usedthe methods of analytical mechanics, mathematical design, analytical and numeral decision of equalizations and systems of nonlinear differential equalizations of the second orderwith impulsive coefficients. Alsonumeral and model experimentshad the place. Results were the foundation toimprove themethod of project calculation vibrationengines with pendulum vibrators. Analysis of oscillation engines with pendulum vibrators and MFM, of known dynamics models and methods of project calculation which applied in practice found out considerable imperfection of these models and methods. The main disadvantage is necessityof the considerable volume of pre-project research experimental works. Such situationis because ofabsence in the dynamics models serialallowof kinetic, power - electromagnetic and mixed indignations and as a result imperfect allowof intensity and mutual influenceof these indignations with impossibility at the level of models to estimate firmness of oscillation engine work. Using the methods of analytical mechanics and mathematical design is improved: model of vibrator base element –spring -balancependulum withkinetic indignation by initiationto the model the elements establishing his position in the vertical oscillation field withkinetic indignation; models of one-pendulum and two-pendulum vibrators which are based on hyperboloidal torsionwithkinetic indignation; oscillation engines dynamics models withone-pendulum and two-pendulumvibrators for the cases of arbitrary and large inflexibility of MFMwithkinetic indignation by development and initiationin the model the transmission function of MFMand single and impulsive management functions of oscillation engine work; dynamics model of one-pendulum vibrator with power - electromagnetic indignation; dynamics models of oscillation engines withone-pendulum and two-pendulum vibrators withkinetic, power -electromagnetic and mixed indignations. It is stated ahigh-quality difference, novelty and enhancement reflection theoscillation engines dynamicswith mixed indignationbythe improved models. These models have the possibilityto be used forresearch of oscillation engines dynamics and project calculation not only as drivingsystems of servo-mechanisms on an oscillation equipment but also for the drivingof basic and auxiliary mechanisms of other technological equipment with the smoothadjusting of rotation frequency theirentrance billows in a range from 0 to 300 turn/minby help the oscillation engines with pendulum vibrators and MFM. Applyingtheanalytical methods of close decision of equalizations and systems of nonlinear differential equalizations ofthe second order with impulsive coefficients, the ownfrequencies andamplitudesof vibrations of vibrators pendulums are appraised. The criterion of firmness of pendulum vibrators motionwith kinetic, power and mixed indignationsis first got. It is demonstrated that this criterion may be treatedas the criterion of oscillation engines proof work with pendulum vibrators and MFM. The criterion of intensity and mutualestimation of kinetic and power indignations of oscillation engine vibrators which allows to raisequality of adequacy reflection the engines dynamics bythe improved models is first got. The numerical valuesof criterion are defined.After these values is formed the scope of quality applyingthe proper improved models forkinetic, power or mixed indignations. The analysis of dynamics processes got subsequent development on the basis of external mechanical descriptions calculation of oscillation engine with pendulum vibrators and MFMby raising thenumeral experiment. At the estimation of own frequencies and amplitudes of vibrations by analytical methods and theircalculation in a numeral experiment the least divergence with actual values got experimentally discovered for a numeral experiment and made from 7 to 10%. That allows to recommend the analytical methods of these engines dynamics research by the decision of models differential equalizations only as the first approaching of high-quality estimation of adequacy of expected them external mechanical descriptions in a numeral experiment. Experimental determination is improved and external mechanical descriptions of oscillation engines with pendulum vibrators are first got for four types of in-use in practice of MFM engineer by thecalculation and in a model experiment. It is set that oscillation engines are able to generate on an initial billow and smoothingchange a torqueand frequency of rotation in ranges from 0÷1,2 [kN∙m] and from 0÷157 [s -1 ] accordingly at permanent frequency of kinetic, power or mixed indignations in 157 s-1. At combinations of vibrators overall-mass descriptions, inflexibilitytheirelasticsystems, the amounts of vibrators in an engine these limits change with the purpose of receipt setrangeby a requirement specification on planning anengine. The method of oscillation engines project calculation is improved by initiationinit the improved dynamics models of oscillation engines through the usingthe developed systems -FORTRANbasedprograms. Exactness and adequacy of external mechanical descriptions, which were got bycalculation after the improved method confirmed by the model experiment and makes 7÷10%. On the basis tasks of researches which are executed in work it is improved and offered to the usein practicethe method of dynamics research of the mechanical systems withvariable structure. В диссертации приведены теоретические обобщения и новое решение научной задачи, которое выражается в усовершенствовании моделей динамики вибрационных двигателей с маятниковыми вибраторами и механизмом свободного хода (МСХ) при кинетическом, силовом – электромагнитном и смешанном возбуждениях методами аналитической механики, математического моделирования, аналитического и численного решения уравнений и систем нелинейных дифференциальных уравнений второго порядка с импульсными коэффициентами с постановкой численного и натурного экспериментов, результаты которых положены в основу усовершенствования методики проектного расчета этих двигателей. По результатам исследований в практику использования внедрена методика проектного расчета вибрационных двигателей с маятниковыми вибраторами и МСХ при кинетическом, силовом – электромагнитном и смешанном возбуждениях. Предложена к использованию методика исследования механическихсистем переменной структуры.
Усовершенствование моделей динамики вибрационных двигателей с маятниковыми вибраторами
An improvement of oscillation engines dynamics models with pendulum vibrators
Keywords: вібраційний двигун; маятниковий вібратор; механічна система змінної структури; oscillation engine; pendulum vibrator; mechanical system of variable structure; вибрационный двигатель; маятниковый вибратор; механическая система переменной структуры